2022
DOI: 10.1186/s12978-022-01465-z
|View full text |Cite
|
Sign up to set email alerts
|

High coverage but low quality of maternal and newborn health services in the coverage cascade: who is benefitted and left behind in accessing better quality health services in Nepal?

Abstract: Background Antenatal care (ANC) visits, institutional delivery, and postnatal care (PNC) visits are vital to improve the health of mothers and newborns. Despite improved access to these routine maternal and newborn health (MNH) services in Nepal, little is known about the cascade of health service coverage, particularly contact coverage, intervention-specific coverage, and quality-adjusted coverage of MNH services. This study examined the cascade of MNH services coverage, as well as social dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Qualitative studies show that access is also influenced by family relationships and gender norms which limit agency, access to resources, and restrict movement outside the home [ 18 , 19 ]. Health workers and FCHVs are responsible for nutrition counselling during ANC, but there are indications that the quality of this counselling may be sub-optimal [ 20 , 21 ]. Despite the following global guidance to address anaemia in pregnancy, anaemia is an intractable problem in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies show that access is also influenced by family relationships and gender norms which limit agency, access to resources, and restrict movement outside the home [ 18 , 19 ]. Health workers and FCHVs are responsible for nutrition counselling during ANC, but there are indications that the quality of this counselling may be sub-optimal [ 20 , 21 ]. Despite the following global guidance to address anaemia in pregnancy, anaemia is an intractable problem in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to reduce living standard related inequalities in Nepal so that a massive chunk of inequality in MCH services can be reduced. Privileged women in terms of living standards, education, access to financial institutions and other demographic characteristics are often found to utilize optimal quality Maternal and Newborn Health (MNH) services compared to their counterparts despite high coverage of such services [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other ANC quality components have gotten little attention in many LMICs. Evidence suggested that only completion of 4ANC visits does not guarantee the uptake of recommended ANC interventions [ 124 ]. The provision of optimum quality care depends on the health system readiness (e.g., health workforce trained on ANC).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, little research has been done on quality-adjusted coverage in LMICs [ 68 ]. As current literature focuses on the number of contacts as the quality of care, there is a need to measure quality-adjusted coverage using population-level household survey data such as demographic and health surveys [ 124 ]. Quality-adjusted coverage can be improved by focusing on care processes, especially technical quality.…”
Section: Discussionmentioning
confidence: 99%